TAMI-03. PROGNOSTIC SIGNIFICANCE OF NEUTROPHIL-TO-LYMPHOCYTE RATIO (NLR) IN PATIENTS WITH BRAIN METASTASES FROM DIFFERENT TUMOR ORIGINS. (12th November 2021) - Deng, Guanhua; Wen, Lei; Zhou, zhaoming; Shan, Changguo; Lai, Mingyao; Zhou, Cheng; Cai, Linbo
Abstract: PURPOSE: Brain metastases (BMs) represent the most common adult intracranial malignancy. The prognosis of BMs is subject to many factors, i.e., the number, size and locations of the metastatic sites, tumor origins, pathologic types, gene mutation status, metastatic sites, and KPS etc . This study aimed to evaluate the prognostic value of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) in brain metastases. METHODS: A total of 480 patients diagnosed with brain metastases from a wide range of tumor origins, i.e., NSCLC, SCLC, breast cancer, melanoma, prostate, kidney, gastrointestinal cancer, cervical carcinoma, ovarian cancer, choriocarcinoma of uterus were retrospectively analyzed. Pre-radiotherapy NLR, PLR, and LMR were calculated as total neutrophil/lymphocyte, platelet/Lymphocyte, lymphocyte/monocyte, respectively. Survival rates were estimated using the Kaplan-Meier survival analysis. Cox regression models were used to identify independent prognostic factors. RESULTS: The median overall survival (OS) was 14.4 months [95%CI: 13.4-15.5]. The median overall survival after radiotherapy was significantly different between patients with NLR< 4 and those with NLR≥4 (OS 16.3 mo. vs. 12.2 mo., P < 0.0001). No signiﬁcant difference was observed between PLR vs. OS, and LMR vs. OS (PLR< 180: HR=1.221, P =0.240; LMR< 4: HR=0.753, P =0.141). The Cox regression model for the continuous metric values revealed that the NLR increased every 1.0 was associated with additional 5.9% of fatal risk (HR: 1.059; 95%CI = 1.033–1.087, P < 0.0001). NLR was validated as an independent prognostic factor for risk of death after adjusting for sex, age, and KPS. CONCLUSIONS: We revealed pre-treatment NLR is an independent prognostic factor in patients with brain metastases for poor OS, independent of different tumor origins. The NLR warrants further studies using sub-group analysis and validation in external cohorts. Future studies in this parameter have a potential to facilitate more precise risk-stratifications to guide personalized treatment for BM.